Integrating landscape ecology into natural resource management - Liu, Jianguo, 1963-; Taylor, William W. (Cambridge studies in landscape ecology., 2002)
This collaborative work is the first to link landscape ecology to natural resource management. It covers such important issues as biodiversity conservation, land use, natural resource management, ecology and integration of natural and social sciences. This book is aimed at landscape ecologists, natural resource managers, policy makers, and graduate students.